Understanding factors influencing demand of online information goods : a case study on online music store - Qian, Chen Hao (2011)
Previous studies on online information goods primarily focus on how to capture consumers’ surplus from the perspective of sellers. In this paper, we take a different approach and look from the viewpoint of consumers to investigate how consumers’ attitude toward online information goods could be influenced by the products’ attributes. We examine three product dimensions, namely divisibility, product variety and preview availability in three separate experiments on a sample of 240 subjects. Results suggest higher divisibility, higher variety and more preview availability have positive impact on consumers’ likelihood of purchase. These factors also have influence on consumers’ expected demand. In addition, we have also proved the positive correlation between consumers’ expected demand and their preference for fixed fee pricing plan. The study facilitates the understanding about consumers’ behavior in buying online information goods and proposes recommendations to increase consumer demand.